2021
DOI: 10.3390/foods10112791
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sensory Attributes, (Dis) Liking and Volatile Organic Composition of Gorgonzola PDO Cheese

Abstract: Blue-veined cheese tends to polarize the consumers’ affective responses due to its strong flavor. This study aims to: (i) explore the consumers’ sensory perceptions and liking of Gorgonzola PDO cheese; (ii) identify the sensory drivers of acceptance for Gorgonzola in the function of the cheese style; (iii) characterize them by the volatile organic compounds (VOCs); and (iv) explore the relationships of the VOCs with sensory perception and liking. Six samples of Gorgonzola cheese differing in style (sweet vs. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…VOCs emitted from food products are decisive for the perception of aroma and taste [ 62 ]. Recently, the relationship between VOCs and sensory attributes has been successfully evaluated for Gorgonzola cheese [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…VOCs emitted from food products are decisive for the perception of aroma and taste [ 62 ]. Recently, the relationship between VOCs and sensory attributes has been successfully evaluated for Gorgonzola cheese [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The term 'soapy' was also used in a previous study (Moio, Piombino, & Addeo, 2000) to describe the Italian blue-veined Gorgonzola Protected Designation of Origin (PDO) cheese odor. However, only very recently it was demonstrated that a great phenotypic variability in Gorgonzola cheese liking exists and that differences in preferences for Gorgonzola cheese were mainly linked to the perception of 'soapy' flavor (Torri et al, 2021).…”
Section: Soapy Flavor Perception In Foodmentioning
confidence: 99%
“…Six samples of Gorgonzola PDO cheese varying according to style (Sweet vs Piquant), aging time (70-95 days) and production process (Artisanal vs Industrial) were analyzed. The same samples were used in a previously published paper on Gorgonzola Cheese (Torri et al, 2021). Samples are identified with a letter indicating the cheese style followed by a number referring to the aging time expressed in days.…”
Section: Gorgonzola Pdo Cheese Samplesmentioning
confidence: 99%
See 2 more Smart Citations